Development of the moss Pogonatum urnigerum (Hedw.) P. Beauv. under in vitro culture conditions - Cvetić Tijana; Sabovljević Aneta; Sabovljević M.; Grubišić D. (Archives of Biological Sciences, 2007)
Pogonatum urnigerum (Polytrichaceae) in vitro culture was established from spores collected in nature. Both protonema and gametophore stages of gametophyte development were obtained. Also, a stable callus culture was established using hormone-free nutrient medium. The best nutrient medium for development was half-strength Murashige- Skoog medium supplemented with 1.5% sucrose. Auxin treatment enabled some gametophores to develop, but prolonged treatment induced early senescence. Tissues grown on cytokinin did not produce any gametophytes and did not survive prolonged treatment.